Optimization of particle bombardment parameters for DNA delivery into the male flowers of banana - Mahdavi, Fatemeh; Mahmood, Maziah; Mohd Noor, Normah (Versita, 2014)
The possibility of increasing the efficiency of banana transformation was investigated by particle bombardment of the male flowers of banana plants for constitutive expression of gfp gene. The effects of particle bombardment parameters, such as acceleration pressure, bombardment distance, chamber vacuum pressure, gold microcarrier size, gold quantity, DNA quantity, number of bombardments and pre-culture were examined. Single cauliflower-like bodies (CLBs) clusters, induced from meristemic parts of Musa sapientum cv. Nangka (AAB) male flowers, were bombarded by pCambia1304 plasmid carrying gfp gene driven by the CaMV 35S promoter. Optimal transient expression of green-fluorescent protein (GFP) was obtained when the three-day old cultured tissues were bombarded two times at 1100 psi helium pressure. However, the highest GFP expression was observed when 9 cm was applied as bombardment distance with 28 mmHg chamber vacuum pressure. Gold particle with 1 μm diameter at 60 μg/μL concentrations coated with 1.5 μg/μL of DNA have been used as the optimum bombardment parameter since GFP expression was significantly different compared to other conditions. Application of optimized condition proved effective for the generation of stable transgenic banana plants. PCR and southern blot analyses confirmed the presence and integration of gfp gene in genomic DNA of transformed plants. Transformation frequency achieved with the optimized protocol was 7.5% which was significantly higher than the conventional protocol.